From gut to bone: deciphering the impact of gut microbiota on osteoporosis pathogenesis and management - Hao, Linjie; Yan, Yuzhu; Huang, Guilin (Frontiers in Cellular and Infection Microbiology, 2024)
Osteoporosis (OP) is characterized by decreased bone mineral density (BMD) and increased fracture risk, poses a significant global health burden. Recent research has shed light on the bidirectional relationship between gut microbiota (GM) and bone health, presenting a novel avenue for understanding OP pathogenesis and developing targeted therapeutic interventions. This review provides a comprehensive overview of the GM-bone axis, exploring the impact of GM on OP development and management. We elucidate established risk factors and pathogenesis of OP, delve into the diversity and functional changes of GM in OP. Furthermore, we examine experimental evidence and clinical observations linking alterations in GM composition or function with variations in BMD and fracture risk. Mechanistic insights into microbial mediators of bone health, such as microbial metabolites and products, are discussed. Therapeutic implications, including GM-targeted interventions and dietary strategies, are also explored. Finally, we identify future research directions and challenges in translating these findings into clinical practice.